Penguatan Ekosistem Halal Value Chain sebagai Pengembangan Industri Halal Menuju Era 5.0 - Kholifatul Husna Asri; Amin Ilyas (Neolectura, 2022)
The research method used in this study is a qualitative research, with the type of research being a literature review of several previous studies. The method of data collection is through secondary data obtained from various scientific works such as journals and articles, as well as books, documentation and the internet. Based on the results of the research that the Islamic economy and the halal industry are sectors that have opportunities, opportunities and contribute to added value to the economy through fulfilling market demand. In supporting the development of the sharia economy, one of the efforts is through strengthening the halal value chain which includes a number of industries related to the needs of halal products and services. The halal industrial ecosystem must be strengthened and developed in order to be able to master the potential of the global market. In addition, efforts to develop a halal value chain in the development of the halal industry start from the input to outcome, especially in facing the era of society 5.0. The strengthening of halal value chain includes several sectors including (1) the food and beverage industry consisting of raw materials, manufactures, retailers, financing, distribution channels and technology. (2) stakeholders , namely (a) government, (b) consumers, (c) industry and (d) investors. Stakeholdersa role as facilitators and catalysts that connect demand and supply in the halal industry..